A first record of mealybug, Planococcus bendovi Williams (Hemiptera: Coccomorpha: Pseudococcidae) in Southeast Asia - Zarkani, Agustin; Nadrawati,; Djamilah,; Sunardi, Tri; Priyatiningsih,; Apriyanto, Dwinardi; Ercan, Cansu; Kaydan, Mehmet Bora (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Planococcus bendovi Williams (Hemiptera: Coccomorpha: Pseudococcidae) is a mealybug species that holotype and paratypes specimens were only recorded from India as a single slide. A series of surveys have been set up in Bengkulu province, Indonesia in 2021 and recorded the occurrence of P. bendovi in the country. The species was found on the leaves, trunks, and branches of a semi-parasitic plant, Loranthus pentandrus L. (Loranthaceae). This is the first report of P. bendovi in Indonesia as well as Southeast Asia.